Application of RACI Framework for optimization of Key Performance Indicators (KPI) in manufacturing companies - I Made Sondra Wijaya; M. Ansyar Bora; Ririt Dwiputri Permatasari; Melda Andhini Fhasya Zulkarnaian (Dinasti Publisher, 2025)
This study successfully formulates effective Key Performance Indicators (KPIs) for measuring company performance using the RACI framework at PT XYZ Batam. The RACI framework, which identifies roles and responsibilities as Responsible, Accountable, Consulted, and Informed, is applied to ensure that each performance measurement aspect receives appropriate and accurate assessment. This research covers the identification of relevant KPIs in three key areas: work discipline, Occupational Health and Safety (OHS), and work environment. Through surveys and interviews with company stakeholders, the selected KPIs are then correlated with RACI roles to determine the weight of each role’s contribution to achieving the KPIs. The results indicate that the application of the RACI framework enhances accountability and collaboration between departments, as well as facilitates more effective performance monitoring and evaluation. The RACI and KPI weighting matrix produced by this study provides clear guidance for PT XYZ Batam in managing the company's performance holistically and systematically.